Exposure to secondhand tobacco smoke and the frailty syndrome in US older adults - García-Esquinas, Esther (Age (Dordr), 2015)
Exposure to secondhand tobacco smoke (SHS) is a well-established risk factor for cardiovascular disease and lung cancer in nonsmoking adults. However, few studies have focused on the health consequences of exposure to SHS in older adults. This is the first study to assess the association between SHS and the frailty syndrome in the nonsmoking older adult population. Cross-sectional study was conducted among 2059 nonsmoking adults aged ≥60 years who participated in the third US National Health and Nutrition Examination Survey and had completed a physical examination. Exposure to SHS was assessed by serum cotinine concentrations and by self-reported data from the home questionnaire. Frailty was ascertained with a slight modification of the Fried criteria. Analyses were performed with logistic regression and adjusted for the main confounders. The median (interquartile range) concentration of serum cotinine was 0.095 (IQR 0.035–0.211) ng/mL. The prevalence of frailty was 6.0 %. The odds ratios (95 % confidence interval [CI]) of frailty comparing the second, third, and fourth to the lowest quartile of serum cotinine were, respectively, 1.44 (0.67–3.06), 1.46 (0.75–2.85), and 2.51 (1.06–5.95), p value for trend 0.04. An increased frequency of frailty was also observed in participants reporting to live with ≥2 smokers at home (odds ratio 5.37; 95 % CI 1.13–25.5). In the US nonsmoking older adult population, exposure to SHS was associated with an increased frequency of frailty. More efforts are needed to protect older adults from SHS, especially at home and in other areas not covered by smoke-free regulations.